2014
DOI: 10.1097/sap.0b013e3182773ed2
|View full text |Cite
|
Sign up to set email alerts
|

Combined Carbon Dioxide Laser with Photodynamic Therapy for Nodular and Superficial Basal Cell Carcinoma

Abstract: Combined CO2 laser and PDT have equivalent cure rates to surgery for BCCs--notably of the nodular subtype--these modalities acting synergistically. This strategy provides cure often with scarless outcomes as illustrated. Laser with PDT is most appropriate for patients who value excellent cosmetic outcomes and where avoidance of an invasive procedure is an important factor. In addition, this modality comes into its own for specific groups of patients, such as those on Warfarin or those with diffuse or multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
(3 reference statements)
0
17
0
2
Order By: Relevance
“…Previous studies found similarly high efficacy in CL + PDT for BCC, but results in FL + PDT are varying. Shokrollahi et al . observed 97.1% CR after one to three CL + PDT sessions in 177 BCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found similarly high efficacy in CL + PDT for BCC, but results in FL + PDT are varying. Shokrollahi et al . observed 97.1% CR after one to three CL + PDT sessions in 177 BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalence analysis was performed with the ‘Tango's score confidence interval for a difference of proportions with matched pairs’ (α = 0.025). The equivalence margin δ = 16.1% was based on existing literature by computing the difference in a clinical assessed efficacy of 97.1% found for CL + PDT and of 81% for FL + PDT . The chosen value of δ is a rough estimate because these studies treated nodular BCC (nBCC) or the broad spectrum of BCC and a δ value of 16,1% is rather substantial from a clinical viewpoint.…”
Section: Methodsmentioning
confidence: 99%
“…Photodynamic therapy increases BCC recurrences so modifications to PDT have been tested. Day/light‐mediated PDT, AXFL‐mediated PDT and PDT combined with CO 2 laser and Er:YAG laser have been attempted. Also, light fractionation can improve the response of BCC to PDT .…”
Section: Discussionmentioning
confidence: 99%
“…The Gunning Fog median was 12.25 (9.5-17.4). The Coleman-Liao Index showed a grade median of 10.5 (8)(9)(10)(11)(12)(13)(14). The Automated Readability Index and Linsear Write Formula grade medians were 9.5 (6.5-12.7) and 11.05 (7.3-15.9), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment for skin cancer is wide ranging, and while surgical excision with a margin of non-involved tissue is typically favoured in Europe and the USA [5], many other options for non-melanoma skin cancer exist, such a topical chemotherapy [6], radiotherapy [7] and in some cases laser treatment [8]. In today's era of shared decision-making between patient and clinician, all feasible options should be discussed with the patient [9].…”
Section: Introductionmentioning
confidence: 99%